Utilization of Corn Cob Waste into Briquettes as Renewable Fuel in Nagari Lingkuang Aua Bandarajo - Syolendra, Dwi Finna; Riga, Riga; Away, Romy Dwipa Yamesa; Saputra, Boni; Mulia, Melindra; Fitri, Bali Yana; Hidayanti, Ermia (Fakultas MIPA Universitas Negeri Padang, 2024)
Pasaman District is the largest corn producer in West Sumatra Province, one of the villages is Lingkuang Aua Bandarajo, where the majority of the population work as corn farmers. This amount is directly proportional to the amount of corn cob waste produced from agricultural activities. Based on the results of observations and interviews with local communities, it is known that the processing of corn cob waste has not been carried out optimally, because people tend to burn the corn cobs, which has an impact on environmental pollution. One solution that can be provided is to hold training on processing corn cob waste into charcoal briquettes. This PKM activity was carried out offline with 3 sessions, namely a session presenting material regarding business opportunities and how to make corn cob briquettes, practice accompanied by a team and independent practice. Through this PKM activity, it is known that there has been an increase in knowledge about corn cob briquettes by the youth of the village of Aua Bandarajo. The corn cob briquettes produced can be a source of renewable fuel and can also improve the economy of local communities.